HYBRID CRYPTOGRAPHIC APPROACH FOR INTERNET OFHYBRID CRYPTOGRAPHIC APPROACH FOR INTERNET OFTHINGS APPLICATIONS: A REVIEW (Journal of Information and Communication Technology, 2020)
Cryptography is described as the study of encrypting or secretCryptography is described as the study of encrypting or secretwriting of data using logical and mathematical principles toprotect information. This technique has grown in importancein computing technologies for banking services, medicalsystems, transportation and other Internet of Things (IoT)-based applications which have been subjected to increasingsecurity concerns. In cryptography, each scheme is built withits own respective strength, but the implementation of singlecryptographic scheme into the system has some disadvantages.For instance, symmetric encryption method provides a costeffectivetechnique of securing data without compromisingsecurity. However, sharing the secret key is a vital problem. Onthe other hand the asymmetric scheme solves the secret keydistribution issue; yet the standalone technique is slow andconsumes more computer resources compared to the symmetricencryption. In contrast, hashing function generates a unique andfixed-length signature for a message to provide data integritybut the method is only a one-way function which is infeasibleto invert. As an alternative to solve the security weakness of every single scheme, integration of several cryptographicof every single scheme, integration of several cryptographicschemes which are also called the hybridization techniqueis being proposed offering the efficiency of securing data andsolving the issue of key distribution. Herein, a review study ofarticles related to hybrid cryptographic approach from 2013to 2018 is presented. Current IoT domains that implementedhybrid approaches were identified and the review was conductedaccording to the category of the domain. The significant findingsfrom this literature review included the exploration of variousIoT domains that implemented hybrid cryptographic techniquesfor improving performance in related works. From the findings,it can be concluded that the hybrid cryptographic approach hasbeen implemented in many IoT cloud computing services. Inaddition, AES and ECC have been found to be the most popularmethods used in the hybrid approach due to its computing speedand security resistance among other schemes.